Cybersecurity risk awareness in mobile banking: evidence from Sabah, Malaysia - Mohidin, Rosle; Lajuni , Nelson; Lestari, Rahayu; Wastuti, Wahyu; Budin , Dg Safrina Ag; Ogunkoya, Olufemi Adewale; Dewi, Monica; Muharam, Hari; Salmah (Ifma Publishing, 2025)
This study investigates how Sabahan perceive and respond to cybersecurity risks when using mobile banking. This study employed partial least squares structural equation modeling (PLS-SEM) and focused on four main factors: user awareness and behavior (UAB), mobile device security (MDS), banking app security features (BASF), and perceived cybersecurity threats (CT). A total of 350 questionnaires were distributed, and 286 valid responses were analyzed. The results indicate that UAB, MDS, and BASF all play a significant role in shaping cybersecurity risk awareness (CRA), while CT showed little to no direct effect. These findings suggest that improving user education and promoting secure practices are just as important as technical safeguards. In particular, enhancing digital literacy among less tech-savvy users, ensuring that security features are simple to use, and strengthening device protections can all help reduce risks of cybersecurity. The study concludes that a combination of user-focused education and stronger security standards is necessary to improve the overall safety of mobile banking services.